Здравствуй, Удмуртия - Грязев Георгий Геннадьевич (Удмуртия, 2016)
Экземпляры: СБ (20160830) / Инвентарный номер: 52457 / Цена: 396.00 / Сис.шифр: 26.89 (2Рос. Удм) / Авт.знак: З-46 / ГРНТИ: 39 / ББК: 26.89 (2Рос. Удм)